2003
DOI: 10.1359/jbmr.2003.18.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Gene Polymorphisms and Peak Bone Density in Chinese Nuclear Families

Abstract: PBD is an important determinant of osteoporotic fractures. Few studies were performed to search for genes underlying PBD variation in Chinese populations. We tested linkage and/or association of the estrogen receptor ␣ gene polymorphism with PBD in 401 Chinese nuclear families. This study suggests the ER-␣ gene may have some minor effects on PBM variation in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 78 publications
2
44
2
Order By: Relevance
“…Suggestive within-family association was obtained between (TA) 18 and spine BMD (P=0.035), which explained only about 2.42% of total variation even if we assume the within-family association to be significant. For BMI, we obtained suggestive withinfamily association at the (TA) 15 (P=0.043) and (TA) 24 (P=0.021) alleles, and suggestive total association with (Qin et al 2003). In the present study, no significant linkage was found with either BMD or BMI (Table 3).…”
Section: Qtdt Analysissupporting
confidence: 46%
See 2 more Smart Citations
“…Suggestive within-family association was obtained between (TA) 18 and spine BMD (P=0.035), which explained only about 2.42% of total variation even if we assume the within-family association to be significant. For BMI, we obtained suggestive withinfamily association at the (TA) 15 (P=0.043) and (TA) 24 (P=0.021) alleles, and suggestive total association with (Qin et al 2003). In the present study, no significant linkage was found with either BMD or BMI (Table 3).…”
Section: Qtdt Analysissupporting
confidence: 46%
“…The subjects in this study came from our previous study (Qin et al 2003), which was approved by the Research Administration Departments of the Shanghai Sixth People's Hospital and Hunan Normal University. Each nuclear family comprised both parents and at least one female child aged between 20 and 45 years.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study subjects were selected from 401 nuclear families used in our earlier study (Qin et al 2003), which was approved by the Research Administration Departments of Shanghai's Sixth People's Hospital and Hunan Normal University. All subjects were recruited from Shanghai local residents.…”
Section: Subjectsmentioning
confidence: 99%
“…The latter has more than 80% power to test a candidate gene as a quantitative trait loci (QTL) and can explain about 10% of the bone phenotype variation [1,13,18,19] . Using the female-offspring nuclear families, we not only detected an association between Myostatin polymorphisms and BMD variation, but we also successfully observed that genetic polymorphisms in estrogen receptor α and collagen1α2 likely influenced the attainment of peak BMD in Chinese females [1,18,20] . In addition, our latest study of genetic variants in the vitamin D receptor in relation to peak BMD in our male-offspring nuclear families detected an association [15] .…”
Section: Discussionmentioning
confidence: 99%